FAUNA OF COLEPTERA,TENEBRIORIDAE OF ARID COASTAL AND ISLAND ECOSYSTEMS OF THE CASPIAN SEA. - G. M. Abdurakhmanov; M. V. Nabozhenko (Юг России: экология, развитие)
Aim. The aim of the given paper is to expose species structure and geographical distribution of Coleoptera, Tenebrioridae (C, T) of coastal and island ecosystem of the Caspian Sea. The given report is compiled of the matcrials, collected in different periods by authors (1961-2013) in the Caucasian part of the Caspian Sea, in the south of the European part of the Russian Federation, Kazakhstan, islands (the Chechen island, the Nord island. The Tuleniyisland. The Kulaly island), collective materials (ZIN; RAS, museum of Zoology of MSU, Institute NAN of Azerbaijan, National museum of Georgia) and materials published (Kryzhanovsky, 1965, Medvedev, 1987, 1990; Medvedev, Nepesova, 1990; Shuster, 1934; Kaluzhnaya, 1982; Arzanov and others, 2004, Egorov, 2006).Methods. We used the traditional methods of collecting (hand picking, traps soil, soil traps light amplification light traps), processing and material definition. List of species composition discussed fauna composed by modern taxonomy using directories. Location. Coastal and island ecosystems of the Caspian sea.Results. Species structure and data on general and regional distribution of C,T of coastal and island ecosystems of the Caspian Sea is represented in the paper. Faund discussed is widely represented in the fauna of arid regions of land, especially in the fauna of subtropical deserts and semideserts.Main conclusions. Results of the study will be a step in the determination of age of the islands through the biological diversity and the consequent level regime of the Caspian Sea, as well as possible changes in the population structure of darkling beetles (Coleoptera: Tenebrionidae) on island ecosystems.